1999
DOI: 10.1152/ajpheart.1999.277.5.h1849
|View full text |Cite
|
Sign up to set email alerts
|

Inhaled nitric oxide inhibits NOS activity in lambs: potential mechanism for rebound pulmonary hypertension

Abstract: Life-threatening increases in pulmonary vascular resistance have been noted on acute withdrawal of inhaled nitric oxide (NO), although the mechanisms remain unknown. In vitro data suggest that exogenous NO exposure inhibits endothelial NO synthase (NOS) activity. Thus the objectives of this study were to determine the effects of inhaled NO therapy and its acute withdrawal on endogenous NOS activity and gene expression in vivo in the intact lamb. Six 1-mo-old lambs were mechanically ventilated and instrumented … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

5
88
1
1

Year Published

2000
2000
2011
2011

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 70 publications
(95 citation statements)
references
References 28 publications
5
88
1
1
Order By: Relevance
“…Most studies have demonstrated that eNOS levels in the pulmonary vascular endothelium remain unchanged during iNO withdrawal, suggesting that inactivation or down-regulation of eNOS is one of the mechanisms of rebound pulmonary hypertension. 72,73 Inhaled NO also increases plasma endothelin-1 concentrations without enhancing gene expression in lamb. Endothelin-1 receptor blockade prevents the increase in pulmonary vascular resistance after NO withdrawal, indicating a role for endothelin-1 in rebound pulmonary hypertension.…”
Section: Rebound Pulmonary Hypertension and Hypoxemiamentioning
confidence: 99%
See 1 more Smart Citation
“…Most studies have demonstrated that eNOS levels in the pulmonary vascular endothelium remain unchanged during iNO withdrawal, suggesting that inactivation or down-regulation of eNOS is one of the mechanisms of rebound pulmonary hypertension. 72,73 Inhaled NO also increases plasma endothelin-1 concentrations without enhancing gene expression in lamb. Endothelin-1 receptor blockade prevents the increase in pulmonary vascular resistance after NO withdrawal, indicating a role for endothelin-1 in rebound pulmonary hypertension.…”
Section: Rebound Pulmonary Hypertension and Hypoxemiamentioning
confidence: 99%
“…A reaction between NO and O 2 -would produce peroxynitrite, which could then inactivate eNOS protein. 72,74,76 Endothelin-1 receptor antagonists may prevent rebound pulmonary hypertension by protecting endogenous eNOS activity during iNO therapy. 74 To prevent rebound pulmonary hypertension, iNO should be tapered off progressively without any attempt to terminate it if FIO 2 is higher than 50%.…”
Section: Rebound Pulmonary Hypertension and Hypoxemiamentioning
confidence: 99%
“…NO stimulates the release of soluble guanylate cyclase from the tissues, with a consequent increase in cGMP. INO reduces the endogenous NO production as a negative feedback mechanism, and this mechanism is assumed to be related to the rebound reaction to INO withdrawal (1,2,9). We have previously found that the production and/or release of the vasoconstrictor peptide endothelin-1 (ET-1) and possibly of other vasoconstrictors is also related to the rebound, and this may be even more important than the downregulation of endogenous NO production by INO (5).…”
mentioning
confidence: 99%
“…In addition, ET-1-stimulated secondary release of TxA 2 is one of the main modes of signal transduction in ET-1-induced vasoconstriction (21). PGI 2 and TxA 2 , and PGF 2␣ , are important mutually antagonistic vasodilator and vasoconstrictor products, respectively, of arachidonic acid. They are synthesized via a cyclooxygenase (COX)-dependent pathway.…”
mentioning
confidence: 99%
See 1 more Smart Citation